2013
DOI: 10.5194/acp-13-11661-2013
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of chlorine radical with submicron palmitic acid particles: kinetic measurements and product identification

Abstract: Abstract. The heterogeneous reaction of Clq radicals with submicron palmitic acid (PA) particles was studied in an aerosol flow tube in the presence or in the absence of O 2 . Fine particles were generated by homogeneous condensation of PA vapours and introduced into the reactor, where chlorine atoms were produced by photolysis of Cl 2 using UV lamps surrounding the reactor. The effective reactive uptake coefficient (γ ) has been determined from the rate loss of PA measured by gas chromatography-mass spectrome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…MVK and MACR are formed with gas-phase yields of 29 and 21 % (with some variations, depending on NO x levels), respectively (Galloway et al, 2011). Bulk aqueous-phase experiments have shown that also MACR efficiently forms oligomers in the aqueous phase Liu et al, 2009;Michaud et al, 2009), but mechanistic information as detailed as for MVK is not available. MACR is less soluble than MVK (K H,MACR = 6.5 M atm −1 , Iraci et al, 1999), but it has a slightly higher rate constant with OH in the aqueous phase, k MACROH = 9.4 × 10 9 M −1 s −1 .…”
Section: Solubility and Abundance Of Oligomer Precursorsmentioning
confidence: 99%
“…MVK and MACR are formed with gas-phase yields of 29 and 21 % (with some variations, depending on NO x levels), respectively (Galloway et al, 2011). Bulk aqueous-phase experiments have shown that also MACR efficiently forms oligomers in the aqueous phase Liu et al, 2009;Michaud et al, 2009), but mechanistic information as detailed as for MVK is not available. MACR is less soluble than MVK (K H,MACR = 6.5 M atm −1 , Iraci et al, 1999), but it has a slightly higher rate constant with OH in the aqueous phase, k MACROH = 9.4 × 10 9 M −1 s −1 .…”
Section: Solubility and Abundance Of Oligomer Precursorsmentioning
confidence: 99%
“…Reactions of chlorine atoms with polyatomic hydrocarbons represent a vast body of important chemical events in atmospheric chemistry, notably as a source to form complex and highly reactive hydrocarbon radicals via metathesis reactions. , Chlorine atom is indeed a powerful oxidizing agent involved in some major environmental issues such as the ozone-destruction cycle, the oxidation of volatile organic compounds in marine boundary layers , and Polar regions, , the burning of hazardous waste, , and possibly the aging of organic aerosols by heterogeneous processes. Numerous kinetics studies have shown evidence of the high efficiency of hydrocarbon decomposition by Cl atoms. , These reactions are faster than those with the hydroxyl radical OH by at least 1 order of magnitude, although OH is the primary daytime oxidant in the atmosphere. Interestingly, recent observations show evidence for an active chlorine chemistry in the interstellar medium, but its potential role in space has so far hardly been explored. , Studying Cl + RH reactions is also useful to gain a detailed understanding of combustion chemistry as exemplars of the free radical abstraction of hydrogen atoms in saturated hydrocarbons. , The high dimensionality and complexity of the potential energy surfaces (PESs), combined with experimental feasibility, are finally a central motivation to undertake detailed dynamics studies of Cl + RH reactions. …”
Section: Introductionmentioning
confidence: 99%
“…MVK and MACR are formed with gas-phase yields of 29 and 21 % (with some variations, depending on NO x levels), respectively (Galloway et al, 2011). Bulk aqueous-phase experiments have shown that also MACR efficiently forms oligomers in the aqueous phase (El Haddad et al, 2009;Liu et al, 2009;Michaud et al, 2009), but mechanistic information as detailed as for MVK is not available. MACR is less soluble than MVK (K H,MACR = 6.5 M atm −1 , Iraci et al, 1999), but it has a slightly higher rate constant with OH in the aqueous phase, k MACROH = 9.4 × 10 9 M −1 s −1 .…”
Section: Solubility and Abundance Of Oligomer Precursorsmentioning
confidence: 99%